Critical thinking ability and information literacy in identifying fake news on social media users - Ina Hayatun Niza; Marty Mawarpury; Arum Sulistyani; Risana Rachmatan (Jurnal Psikologi Terapan dan Pendidikan, 2022)
Information literacy is an ability that a person needs to be able to use information correctly and identify fake news on social media. Critical thinking skills are skills related to information literacy that can help information consumers identify reliable sources while denying fake news (hoax). The purpose of this study was to determine the relationship between critical thinking skills and information literacy in identifying fake news on social media users. This study uses a quantitative approach with a sample size of 348 people with early adults characterisctics living in Aceh aged 20-34 years and using social media. Data analysis used the Pearson Correlation technique which showed the correlation coefficient r=0.589 with a significance value p=0.000 (p<0.05). The results of the study concluded that there was a positive relationship between critical thinking skills and information literacy on social media users. The majority of the research samples are in the high category for their critical thinking skills and information literacy.